The EU response to the migration crisis. Special reference to the temporary protection directive in the following of the Ukraine war - Alberto Valdés, Ignacio (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2025)
Following the massive influx of people arriving at the external borders of the European Union as a consequence of the Syrian refugee crisis in 2015 and the Russian invasion of Ukraine in 2022, the community institutions had to adopt various measures to provide an effective response to the risk of collapse of national asylum systems in the face of a high number of asylum and refuge seekers. In this context, this work aims to address three protection instruments: (i) the resettlement as a lasting mechanism for the integration of migrants; (ii) the relocation as a specific protection instrument to which especially vulnerable people will benefit; and (iii) the execution of Directive 2001/55/EC as an appropriate solution to the Ukrainian exodus